Creative Value Chains - Benhamou, Yaniv (Bristol University Press, 2026)
Available open access digitally under CC-BY-NC-ND licence. Creative industries are increasingly dominated by digital platforms, yet the distribution of value within these sectors, from music and video games to visual arts, remains deeply unequal. Recent examples include the remuneration of artists on streaming platforms and the use of creative works in AI training data. This imbalance threatens human creativity and cultural diversity. In this book, Benhamou exposes the flaws in current models of value allocation and the inequities embedded within copyright systems. Focusing on the often-overlooked contributors to creative works, the book advocates rethinking copyright and contract through a lens of distributive justice to ensure equitable compensation for all stakeholders in the creative process, including individual creators, invisible workers and digital workers.